CEO Human Capital and Digital Product Innovation: A Dynamic Managerial Capabilities Perspective - Schulz, Colin; Bendig, David; Kriebel, Johannes; Haubner, Kathrin; Fainshmidt, Stav (Information Systems Research, 2026)
Practice- and Policy-Oriented Abstract How does the human capital of chief executive officers (CEOs) drive digital product innovation in manufacturing firms? Analyzing data from 216 U.S. firms and over 8,000 new product announcements, this study shows that technological and business knowledge can both enable and inhibit digital product innovation, depending on the external environment. In stable settings, tech-savvy CEOs drive digital product innovation, whereas business-savvy CEOs focus elsewhere. In dynamic environments, these effects reverse. These findings offer a contextual view on the ongoing debate about the value of technological versus business expertise in top management, suggesting that neither type of knowledge is universally beneficial. We also find that CEOs serve as distinct innovation catalysts beyond their top management teams. Follow-up interviews reveal the diverse strategies they use to initiate, develop, and implement digital product innovation in established firms. Based on these findings, the study offers guidance for boards of directors on aligning CEO selection with environmental demands and for CEOs seeking to expand their knowledge base to more effectively foster digital product innovation under varying conditions.